Translation Issues in the Children Comic ‘Donald Duck’ - ., Nurlaila; Nababan, Mangatur; ., Djatmika; Santosa, Riyadi (International Journal of Engineering and Technology, 2018)
This research is conducted as other researches discussing translation issues focused on identifying techniques implemented to translate a specified translation issue rather than identifying all issues which are possible to be obstacles for translators. However, a research covering as many issues as possible becomes important in order to contribute theories and solutions to ease translator’s job. The aim of this research is to identify translation issues in the English version of Donald Duck Comics. The data are texts contained in the comic panel involving words, phrases, clauses and sentences which are potential to be difficulties for translators. Document analysis is employed to collect the data by reading the comic thoroughly, and noting down them. The validation is conducted by focus group discussion involving one translation expert and three members of doctoral program students majoring in translation. The result of this research shows that there are nineteen (19) translation issues involving abbreviation, cultural terms, dialect, ellipsis, humor, idiomatic expressions, informal expressions, interjections, kinship terms, measurement unit terms, non-standard grammatical structure, onomatopoeia, pronoun, proper name, sarcastic expressions, slang, speaking fluency disorder, swearing and wordplay. The result of this research can be developed into a translation model providing a translation issues mapping along with translation techniques choices which can be used as a translators’ guide.